x平方-4x+2y+6y+13=0则x= y=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 19:51:58
x平方-4x+2y+6y+13=0则x=y=?x平方-4x+2y+6y+13=0则x=y=?x平方-4x+2y+6y+13=0则x=y=?2y错了即(x²-4x+4)+(y²+6y
x平方-4x+2y+6y+13=0则x= y=?
x平方-4x+2y+6y+13=0则x= y=?
x平方-4x+2y+6y+13=0则x= y=?
2y错了
即(x²-4x+4)+(y²+6y+9)=0
(x-2)²+(y+3)²=0
所以x-2=0,y+3=0
x=2,y=-3
X的平方+Y的平方+4X-6Y+13=0
(X的平方+4x+4)+(Y的平方-6Y+9)=0
(x+2)平方+(y-3)平方=0
上式成立必须有x+2=0,且y-3=0
则x=-2,y=3
所以x的y次方=-2的3次方=-8
x平方-4x+2y+6y+13=0则x= y=?
x平方+y平方+13-6x+4y=0,求:x的y平方
x平方+y平方-4x-6y+13=0 ,求3x+4y
x的平方+y的平方-6x+4y+13=0,求x、y
已知x的平方-4x+y的平方-6y+13=0,求x的平方+2y
x的平方+4x+y的平方-6y+13=0,则(x+2y)(x-2y)的值是多少?
已知X,Y满足x平方+y平方—4x+6y+13=0,求代数式(3x+y)的平方-3(3x-y)(x+y)-(x-3y)(x+3y)
已知x,y满足方程x平方+y平方+4x-6y+13=0,则x的y平方的值是
若x的平方+6x+y的平方-4y+13=0,则,x=(),y=()
若x平方+y平方-4x-6y+13=0,求(x-y)负2次方的值.
若 x平方-4x+y平方+6y+13=0,求2x-y的值.
1.(x-2y)(x+2y)-(x平方+y)(x平方-y) 2.(2x-y)(y+2x)-(2y+x)(2y-x)3.已知:x+y=6,x平方-y平方=48,求x,y的值4.x平方-2x分之x+2 -- x平方-4x+4分之x-1
.先化简再求值:(2x+y)(2x+y)-(2x-y)平方其中X,Y满足X平方+Y平方-2X+4Y+5=0
已知x,y满足:x平方+y平方-4x+6y+13=0求(3x+y)-3(3x-y)(x+y)-(x-3y)(x+3y)=?
已知x平方+4y平方-2x+4y+2=0 求x四次方-y四次方/2x平方+xy-y平方*2x-y/xy-y平方/(x平方+y平方/y)平方
已知x平方+4y平方-2x+4y+2=0 求x四次方-y四次方/2x平方+xy-y平方*2x-y/xy-y平方/(x平方+y平方/y)平方
若|2x-y+5|+(x+2y-4)的平方=0,则(2x-y)的三次方-(x-3y)(y-2x)的平方
x的平方-4x+y的平方+2y+5=0,求x+y